Pace and Problems of Growth of Coarse Grains and Kharif Pulses in Western Rajasthan: an Appraisal - Mruthyunjaya, Mruthyunjaya; Ram, K Anantha; Vyas, K K (Annals of Arid Zone, 2016)
The pace and problems of growth of coarse grains and kharif pulses in western Rajasthan is studied by examining the growth trends in the last 24 years. The analysis indicated that coarse grains are loosing and kharif pulses are gaining area and drought years in recent years are more severe than those in the earlier years. Adoption of improved dry farming practices coupled with diversification of demand for coarse grains is suggested. Expanded procurement operations, adequate credit support, crop insurance and better co-ordination between research centres and development departments are also suggested to improve the performance of these crops.